Effective production of multifunctional magnetic-sensitive biomaterial by an extrusion-based additive manufacturing technique. (11th December 2020) - Rodrigues, A F M; Torres, P M C; Barros, M J S; Presa, R; Ribeiro, N; Abrantes, J C C; Belo, J H; Amaral, J S; Amaral, V S; Bañobre-López, M; Bettencourt, A; Sousa, A; et al.
Abstract: A calcium phosphate (CaP)-based scaffold used as synthetic bone grafts, which smartly combines precise dimensions, controlled porosity and therapeutic functions, presents benefits beyond those offered by conventional practices, although its fabrication is still a challenge. The sintering step normally required to improve the strength of the ceramic scaffolds precludes the addition of any biomolecules or functional particles before this stage. This study presents a proof of concept of multifunctional CaP-based scaffolds, fabricated by additive manufacturing from an innovative ink composition, with potential for bone regeneration, cancer treatment by local magnetic hyperthermia and drug delivery platforms. Highly loaded inks comprising iron-doped hydroxyapatite and β-tricalcium phosphate powders suspended in a chitosan-based solution, in the presence of levofloxacin (LEV) as model drug and magnetic nanoparticles (MNP), were developed. The sintering step was removed from the production process, and the integrity of the printed scaffolds was assured by the polymerization capacity of the ink composite, using genipin as a crosslinking agent. The effects of MNP and LEV on the inks' rheological properties, as well as on the mechanical and structural behaviour of non-doped and iron-doped scaffolds, were evaluated. Magnetic and magneto-thermal response, drug delivery and biological performance, such as cell proliferation in the absence and presence of an applied magnetic field, were also assessed. The addition of a constant amount of MNP in the iron-doped and non-doped CaP-based inks enhances their magnetic response and induction heating, with these effects more pronounced for the iron-doped CaP-based ink. These results suggest a synergistic effect between the iron-doped CaP-based powders and the MNP due to ferro/ferrimagnetic interactions. Furthermore, the iron presence enhances human mesenchymal stem cell metabolic activity and proliferation.